A COMPARATIVE STUDY OF INDIGENOUS AND EXOTIC OIL PALM VARIETIES IN ANDHRA PRADESH: OPPORTUNITIES AND CHALLENGES OF OIL PALM CULTIVATION - P., Nandeeswara Rao; Sara, VijayaLaxmi; Aki, Harshitha; Tandra, Priyanka (International Journal of Research -GRANTHAALAYAH, 2023)
This study investigates the agronomic performance, adaptability, economic viability, and associated challenges of indigenous and exotic oil palm varieties in Andhra Pradesh, India. Recognizing the global significance of the oil palm industry and its growing importance in the region, our research aims to provide valuable insights for sustainable cultivation practices. The comparative analysis includes growth parameters, yield potential, climate resilience, soil adaptation, and economic considerations. Through a carefully designed experimental setup, we assess the performance of selected varieties over time, considering environmental impacts, social considerations, and ethical aspects. The study concludes with recommendations for farmers, policymakers, and stakeholders, aiming to guide decision-making and contribute to the responsible development of the oil palm industry in Andhra Pradesh. comparative study of indigenous and exotic oil palm varieties in Andhra Pradesh can provide valuable insights into the opportunities and challenges of oil palm cultivation in the region. Such a study may encompass various aspects, including agronomic performance, yield potential, adaptability to local conditions, economic viability, and environmental impact.